Peningkatan Pengetahuan Keselamatan dan Kesehatan Kerja (K3) bagi Siswa SMKN 7 Jurusan Produksi Grafika, Jakarta - Antinah Latif; Yessy Yerta Situngkir; Susiani; Mawan Nugraha; M. Yusuf (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Safety culture is the key in the preventing of accidents and occupational diseases in the work environment and industry. Safety culture must be trained since school, especially vocational high school. The results of the literature state that OHS training taught during formal schools has an effect on decreasing working injury incidence (WIs) when they work in industry. Occupational Health and Safety (OHS) training for Vocational High School students majoring in Graphic Production has never been carried out and even there is no subject. Therefore, the OHS training is expected to become a routine training as a provision and familiarize the safety culture in the schools. The aim of this training is to improve the competence of students in SMKN 7 Jakarta majoring in Graphic Production. The method in this training is carried out online using the media zoom meeting for 3 hours with two meetings. This training begins with a general OSH behavior assessment and then the results of the assessment are used as the basis for developing training materials. The training materials were given to students of SMKN 7 majoring in graphic production for class XI. Prior to the implementation of learning, a pre-test of OHS material and post-test was given to determine if there was a change in knowledge after being given OSH training online. Based on the results, online OHS training activities can increase the knowledge of the Graphic Production Department Vocational High School students. It is hoped that the increase in knowledge will become an attitude and behavior so that safety will become a culture in schools